OPTIMALISASI PEMBELAJARAN AL-QUR'AN HADITS MELALUI KEBIJAKAN KURIKULUM MERDEKA DI MTS NURUL ALI - Muzakki, Ahmad; Fawaidi, Badrun (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
This study aims to describe the optimization of the independent learning curriculum in the Qur'an and Hadith lessons at MTs Nurul Ali. The method used in this study is descriptive qualitative using observation and interview methods. Data analysis consists of three stages, namely the data reduction stage by correcting and describing the results of the interview. This research was conducted at MTs Nurul Ali in class VIII which consists of 4 classes. The subjects of the study were teachers of the Qur'an and Hadith lessons. From the results found that Madrasah Tsanawiyah Nurul Ali Sumberbulus as one of the piloting of the Independent Curriculum for the Jember district area, where the method used in the Independent Curriculum learning process, one of which uses a project-based learning method. This method is called Problem Based Learning (PBL) to further improve critical thinking skills, foster student initiative in working, motivate and develop interpersonal relationships in groups. However, in the Al-Qur'an and Hadith lessons, the material still uses K-13 material. The factors are because teachers do not have experience with independent learning, limited time management references, differences in learning access, and minimal skills. So it can be said that the optimization of the independent curriculum at MTs Nurul Ali in the Al-Qur'an Hadith lessons has not been fully optimized.